Epidemic Trends in High Tuberculosis Burden Countries During the Last Three Decades and Feasibility of Achieving the Global Targets at the Country Level - Ding, Cheng; Hu, Ming; Shangguan, Yanwan; Guo, Wanru; Wang, Shuting; Feng, Xuewen; Zhang, Zunjing; Zhang, Ying; Xu, Kaijin (Frontiers in Medicine, 2022)
Objective To estimate the epidemic trends of tuberculosis (TB) in 30 high burden countries (HBCs) over the past 30 years, which is crucial for tracking the status of disease control, especially at the country level. Methods Annual data on incidence and mortality of TB in these 30 HBCs were extracted from the Global Burden of Disease database. The average annual percent change (AAPC) was used to evaluate the trends of incidence and mortality. The trajectory analysis was used to identify different trends among the subgroup countries. The predicted incidence and mortality rates in 2025, 2030, and 2035 were also calculated. Results The incidence and mortality decreased in most of the HBCs. The AAPCs of incidence ranged between −4.0 (Indonesia) and −0.2% (DR Congo) (all p < 0.05). The incidence trends in Lesotho (AAPC: 0%, 95% CI: −0.4, 0.3, p = 0.8) and South Africa (AAPC: −0.2%, 95% CI: −0.5, 0, p = 0.1) were stable, and increased in Kenya with AAPC of 0.1% (95% CI: 0.1, 0.2, p < 0.05). The AAPCs for mortality ranged between −5.8 (Ethiopia) and −0.6% (Central African Republic) (all p < 0.05). The mortality trends in DPR Korea (AAPC: 0.1%, 95% CI: −0.3, 0.4, p = 0.6) and Russian Federation (AAPC: −0.5%, 95% CI: −1.9, 0.9, p = 0.5) were stable, and increased in Lesotho and Zimbabwe with AAPC of 1.3% (95% CI: 1.1, 1.4, p < 0.05) and 1.6% (95% CI: 1.0, 2.2, p < 0.05), respectively. Trajectory analysis showed that the Central African Republic, Lesotho, Cambodia, Namibia, and South Africa had higher incidences, and the Central African Republic had higher mortality. Brazil and China had relatively lower rates of incidence and mortality. Predictions showed that reduction rates of incidence and mortality could hardly be reached compared with those set for the global targets for the majority HBCs. Conclusions The disease burden of TB has been reduced among the majority HBCs over the last three decades. According to the current control levels, achieving the ambitious global targets at the country level for these 30 HBCs is challenging.